Оптимізація роботи дозувально-фасувального модуля лінії для пакування рідкої продукції в споживчу упаковку - Павлюков, Владислав Ігорович; Чернієнко, Іван Артурович; Шевченко, Сергій Вікторович; Деренівська, Анастасія Василівна (My University, 2023)
Дозувальні модулі входять в склад автоматизованих пакувальних ліній, де їх налаштовують дозування та фасування певної кількості продукту за визначений проміжок часу в різні види упаковки. За об’єкт дослідження прийнято лінію для фасування та пакування рідкого продукту в споживчу упаковку. Предмет дослідження – витрати рідкого продукту під час переміщення в складових елементах дозувально- фасувального модуля. Методами дослідження є аналіз, синтез та алгоритми дискретно- ситуаційного імітаційного моделювання. Automated packaging lines contain dosing modules that can be adjusted by dosing and packaging a specific amount of product for a specific period of time in various types of packaging. For the object of research line for packing and packing liquid product into consumer packaging is adopted. The subject of the study is the flow rate of the liquid product during movement in the constituent elements of the dosage and packaging module. Methods of research are analysis, synthesis and algorithms of discrete situational simulation. Automated packaging lines contain dosing modules that can be adjusted by dosing and packaging a specific amount of product for a specific period of time in various types of packaging. For the object of research line for packing and packing liquid product into consumer packaging is adopted. The subject of the study is the flow rate of the liquid product during movement in the constituent elements of the dosage and packaging module. Methods of research are analysis, synthesis and algorithms of discrete situational simulation. Automated packaging lines contain dosing modules that can be adjusted by dosing and packaging a specific amount of product for a specific period of time in various types of packaging. For the object of research Line of packing and packing liquid product into consumer packaging is adopted. The subject of the study is the flow rate of the liquid product during movement of the constituent elements of the dosage and packaging module. Methods of research are analysis, synthesis and algorithms of discrete situational simulation.
Keywords: дозувально-фасувальний модуль; пакувальна лінія; споживча упаковка; рідка продукція; dosing and filling module; packaging line; consumer packaging; liquid product; кафедра мехатроніки та пакувальної техніки